Effects of Selenite and Genistein on G(2)/M Cell Cycle Arrest and Apoptosis in Human Prostate Cancer Cells - Zhao, Rui (2009)
Combination of chemopreventive agents with distinct molecular mechanisms is considered to offer a potential for enhancing cancer prevention efficacy while minimizing toxicity. Here we report two chemopreventive agents, selenite and genistein, that have synergistic effects on apoptosis, cell cycle arrest, and associated signaling pathways in p53-expressing LNCaP and p53-null PC3 prostate cancer cells. We show that selenite induced apoptosis only, whereas genistein induced both apoptosis and G(2)/M cell cycle arrest. Combination of these two agents exhibited enhanced effects, which were slightly greater in LNCaP than PC3 cells. Selenite or genistein alone upregulated protein levels of p53 in LNCaP cells only and p21(waf1) and Bax in both cell lines. Additionally, genistein inhibited AKT phosphorylation. Downregulation of AKT by siRNA caused apoptosis and G(2)/M cell cycle arrest and masked the effects of genistein. Treatment with insulin-like growth factor I (IGF-I) elevated levels of total and phosphorylated AKT and suppressed the effects of genistein. Neither downregulation of AKT nor IGF-I treatment altered the cellular effects of selenite. Our study demonstrates that selenium and genistein act via different molecular mechanisms and exhibit enhanced anticancer effects, suggesting that a combination of selenium and genistein may offer better efficacy and reduction of toxicity in prostate cancer prevention.